Volatile Bioactive Compounds from Lasiodiplodia pseudotheobromae IBRL OS-64, an Endophytic Fungus Residing in the Leaf of Ocimum sanctum - Mohd Taufiq Mat Jalil; Darah Ibrahim (HAYATI Journal of Biosciences, 2022)
Endophytic fungi are known as potential novel compound producers with promising antimicrobial activities. Hence, the present study aimed to investigate the possible bioactive compounds present in the ethyl acetate extract of Lasiodiplodia pseudotheobromae IBRL OS-64. The ethyl acetate extract exhibited significant antibacterial activity against both Gram-positive and Gram-negative bacteria in disc diffusion assay. Thin-layer chromatography (TLC) was performed with chloroform, acetone and ethyl acetate (1:2:1, respectively) used as a solvent system and nine spots with diverse polarities were obtained. The TLC chromatogram with the active spot was localized with bioautography assay and the finding revealed that the dark spot with an Rf value of 0.5882 showed good antibacterial activity against all test bacteria. The fraction F5 exhibited promising antibacterial activity upon partial purification of dark spot via column chromatography and the GC-MS analysis of fraction F5 resulted in the detection of a major compound, 2-Benzenedicarboxylic acid, mono (2-ethylhexyl) ester with 90% matching factor. Thus, this compound may greatly contribute to the antibacterial activity of the fraction and has the potential to be developed as an antibiotic. The findings indirectly indicate that fungal endophytes from the medicinal plant could be a potential candidate for bioactive compounds with pharmaceutical properties.